Case Report: Pregnancy complicated with pulmonary arteriovenous malformation—diagnosis and surgical management - Ji, Wenying; Fu, Mingju; wang, Hongquan; He, Zhifen; Chen, Junhao; Fu, Shi; Fu, Yuanzhi; Zhu, Xingcheng (Frontiers in Surgery, 2025)
Pulmonary arteriovenous malformation (PAVM) during pregnancy is a rare but life-threatening condition, exacerbated by gestational hemodynamic changes. This case report describes a 24-year-old gravida at 27 + 6 weeks presenting with recurrent hemoptysis and hypoxemia. Contrast-enhanced transthoracic echocardiography (TTCE) and computed tomography angiography (CTA) confirmed a left upper lobe PAVM. A multidisciplinary team prioritized cesarean delivery under combined spinal-epidural anesthesia to minimize hemodynamic instability, followed by staged transcatheter embolization (TCE) postpartum—marking the first TCE application for PAVM in Yunnan, China. The neonate (1,100 g) demonstrated favorable Apgar scores, and maternal recovery was achieved without recurrence. Key challenges included balancing fetal safety with urgent intervention, optimizing perioperative critical care, and addressing risks of hypoxemia and hemorrhage. This case underscores the efficacy of coordinated obstetrics, anesthesiology, and interventional radiology teams in managing high-risk pregnancies with PAVM. It highlights spinal-epidural anesthesia for hemodynamic stability, TCE as a minimally invasive solution, and the necessity of long-term surveillance for recurrence. These insights advance clinical strategies for rare cardiopulmonary-obstetric emergencies, emphasizing tailored interventions and multidisciplinary collaboration to ensure maternal-fetal safety.